Human lysosomal α-D-mannosidase regulation in promyelocytic leukaemia cells. Issue 6 (15th September 2011) - Urbanelli, Lorena; Magini, Alessandro; Ercolani, Luisa; Trivelli, Francesco; Polchi, Alice; Tancini, Brunella; Emiliani, Carla
Abstract : Lysosomal α-D -mannosidase is an exoglycosidase involved in the ordered degradation of N-linked oligosaccharides. It is ubiquitously expressed, although the main transcript is more abundant in peripheral blood leucocytes. Here we report that α-D -mannosidase enzyme activity is very high in the promyelocytic leukaemia cell lines HL60 and NB4, as compared with other leukaemic cell lines or cells from different human sources. The MAN2B1 transcript level correlates with enzyme activity, indicating a transcriptional up-regulation of the α-D -mannosidase gene. The promoter was then characterized in HEK-293 cells (human embryonic kidney 293 cells) and HL60 cells; regulatory sequences crucial for its activity were determined by reporter gene assay in HEK-293 cells and located in the region −101/−71 with respect to the first ATG codon. Supershift assay demonstrated that Sp1 (specificity protein 1) bound to this sequence both in HEK-293 and HL60 cells. However, 5′-RACE (5′-rapid amplification of cDNA ends) indicated the use of multiple upstream TSSs (transcription start sites) in HL60 with respect to HEK-293 cells and gel shift analysis of the sequence −373/−269 demonstrated a specific binding by NF-κB (nuclear factor κB) transcription factor in HL60 but not in HEK-293 cells. We concluded that despite the α-D -mannosidase promoter showing typical features of housekeeping gene promoters, α-D -mannosidase transcription is specifically regulated in HL60 by NF-κB transcription factor.